2019
DOI: 10.1002/wrna.1533
|View full text |Cite
|
Sign up to set email alerts
|

miR‐146a‐5p: Expression, regulation, and functions in cancer

Abstract: Cancer as we know it is actually an umbrella term for over 100 very unique malignancies in various tissues throughout the human body. Each type, and even subtype of cancer, has different genetic, epigenetic, and other cellular events responsible for malignant development and metastasis. Recent work has indicated that microRNAs (miRNAs) play a major role in these processes, sometimes by promoting cancer growth and other times by suppressing tumorigenesis. miRNAs are small, noncoding RNAs that negatively regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
133
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 154 publications
(148 citation statements)
references
References 135 publications
(248 reference statements)
5
133
0
Order By: Relevance
“…Moreover, the EGFR gene is regulated via miR‐146a in prostate cancer cells . These results show that miR‐146a affects human prostatic epithelial cells through many pathways . These researches suggest that miR‐146a may play a significant role in controlling cancer by modulating the immune system.…”
Section: Mir‐146a In Papillomavirusesmentioning
confidence: 81%
See 4 more Smart Citations
“…Moreover, the EGFR gene is regulated via miR‐146a in prostate cancer cells . These results show that miR‐146a affects human prostatic epithelial cells through many pathways . These researches suggest that miR‐146a may play a significant role in controlling cancer by modulating the immune system.…”
Section: Mir‐146a In Papillomavirusesmentioning
confidence: 81%
“…Although apoptosis frequency is not affected, more cells shifts to S‐phase, indicating enhanced proliferation rates . These results are significant because the decrease of TRAF6 and IRAK 1 expression is formerly reported to have anticancer effects . This miRNA is well investigated in prostate malignancy, and all studies have reported that miR‐146a acts as a tumor inhibitor in prostate cancer.…”
Section: Mir‐146a In Papillomavirusesmentioning
confidence: 91%
See 3 more Smart Citations